Documentation of illnesses’ work-relatedness and effect to work ability in electronic health records of occupational health services - Nissinen, Sari Päivikki; Soini, Satu; Tarvainen, Kimmo; Kangas, Pauliina; Leino, Timo (Finnish Journal of eHealth and eWelfare, 2021)
In occupational health services, it has been recommended that patients’ work-related illnesses will always be clarified and documented in electronic health records to facilitate the follow-ups. The documentation should be made systematically, including assessments of patients’ work-related illnesses or symptoms and the effect on work ability. The purpose of the study was to find out occupational health physicians’ and nurses’ documentation of illnesses’ work-relatedness and effects on work ability in electronic health records. An electronic questionnaire was sent to occupational health physicians and nurses in 2017 and was answered by 295 people. The results showed that the documentation of the assessments of illness’ work-relatedness and effects on work ability is forced functionality in electronic health records. This functionality is most often a forced function for occupational health physicians rather than nurses. Many respondents told that they document the assessments using electronic health record’s default options of a ready-made classification, such as the “not assessed” option. This was more common among general physicians working in occupational health services than physicians specialized or specializing in occupational health. The uniform documentation of illness’ work-relatedness and effects on work ability in electronic health records contributes to identifying the patient’s work ability risks, and benefits the preventive work carried out by occupational health professionals. According to the results, the documentation structures in electronic health records and the documentation methods of occupational health physicians and nurses need to be improved.